2018
DOI: 10.31643/2018/6445.21
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic model of the influence of temperature and carbon on the production of ferroalloy and calcium carbide from the basalt of Dubersay deposit

Abstract: The article covers the results of researches on thermodynamic modeling of ferroalloy and calcium carbide obtaining from basalts of deposit Dubersay. The software package HSC-5.1, based on the principle of Gibbs energy minimum uses in the study. The influence of temperature (from 500 to 2500 °C) and the amount of carbon (from 40 to 60 % of the basalt mass) in the basalt–Fe–nC system was determined. It has been established that iron silicides are formed at T ≥ 1300 °C, Si at T ≥ 1400 °C, CaSi and Al at T> 170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The HSC-9.0 (Outokumpu) software package [10] based on the Gibbs minimum energy principle was used for thermodynamic modeling. Previously, the authors used the HSC Chemistry program to study various ferroalloys, and their results were confirmed during the data collection process [11][12][13]. Manganese ore, slag of refined ferromanganese and Shubarkol coal were used as the initial charge materials for TDM.…”
Section: Methodsmentioning
confidence: 99%
“…The HSC-9.0 (Outokumpu) software package [10] based on the Gibbs minimum energy principle was used for thermodynamic modeling. Previously, the authors used the HSC Chemistry program to study various ferroalloys, and their results were confirmed during the data collection process [11][12][13]. Manganese ore, slag of refined ferromanganese and Shubarkol coal were used as the initial charge materials for TDM.…”
Section: Methodsmentioning
confidence: 99%
“…This category of raw materials includes the igneous rock -basalt (igneous rocks according to the data [1] occupy 25-38% of the earth's surface). In the view of the fact that the raw material potential of the basalt is not used fully, we have proposed a technology of simultaneous electro-thermal production of the calcium carbide and ferroalloy from the basalt in order to expand the possibilities of its processing [2][3][4]. The article presents the results of the experimental studies of the kinetics of the extraction of the silicon, aluminum into the ferroalloy and calcium into the calcium carbide from the basalt of the Daubaba deposit, the reserves of which contain 19.4 million tons [5].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…For the complex processing of basalts, the authors have created a new technology for the simultaneous production of two types of productsferroalloy (containing aluminum and silicon) and calcium carbidefrom Kazakhstan basalts, which are currently obtained by various electrothermal methods. Combining the simultaneous production of ferroalloy and calcium carbide will reduce energy consumption by reducing heat losses by the furnace unit and will increase the level of complex processing of raw materials [40][41][42][43]. The technology is based on the following reaction:…”
Section: Introductionmentioning
confidence: 99%